2012
DOI: 10.1111/nin.12015
|View full text |Cite
|
Sign up to set email alerts
|

Embodied empathy‐in‐action: overweight nurses’ experiences of their interactions with overweight patients

Abstract: Obesity is now commonly recognised to be a significant public health issue worldwide with its increasing prevalence frequently described as a global epidemic. In the United Kingdom, primary care nurses are responsible for weight management through the provision of healthy eating advice and support with lifestyle change. However, nurses themselves are not immune to the persistent and pervasive global levels of weight gain. Drawing on a Gadamerian informed phenomenological study of female primary care nurses in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 38 publications
2
40
0
Order By: Relevance
“…, ). Of a total of five qualitative papers, three conducted interviews with nurses (Persson & Martensson , Aranda & McGreevy , Cass et al . ); one conducted interviews and observations at facilities (Faugier et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, ). Of a total of five qualitative papers, three conducted interviews with nurses (Persson & Martensson , Aranda & McGreevy , Cass et al . ); one conducted interviews and observations at facilities (Faugier et al .…”
Section: Resultsmentioning
confidence: 99%
“…). The reasons for this were not been explored in this study, but nurses have indicated struggles with food and weight are related to uncomfortable emotions faced as part of their job (Aranda & McGreevy ).…”
Section: Resultsmentioning
confidence: 99%
“…Stakeholders generally agreed that patients would find advice from a visibly unhealthy nurse as less credible. There is some evidence that nurses who do not lead a healthy lifestyle may be less willing to raise lifestyle issues with patients (Gonz alez et al 2009, Aranda & McGreevy 2014. A recent systematic review showed that patients may be more likely to follow the advice of a healthy healthcare professional (Kelly M., Wills J.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses who engage in unhealthy behaviours may be less willing to intervene and offer health promotion advice for fear of criticism or appearing hypocritical (Aranda & McGreevy, 2014;Beletsioti-Stika & Scriven, 2006;González, Bennasar, Pericàs, Seguí, & De Pedro, 2009;Sejr & Osler, 2002;Sekijima, Seki, & Suzuki, 2005) and patients appear less likely to follow advice given by unhealthy nurses (Hicks et al, 2008;Kelly, Wills, Jester, & Speller, 2017;Kelly, Wills, & Sykes, 2017). Obesity is a visibly unhealthy behaviour and is frequently referred to in the discourse around nurses being healthy role models (e.g.…”
mentioning
confidence: 99%
“…Obesity is a visibly unhealthy behaviour and is frequently referred to in the discourse around nurses being healthy role models (e.g. Aranda & McGreevy, 2014;Naish, 2012;While, 2015).…”
mentioning
confidence: 99%